Shear Strength characteristics of gypseous Soil with Lime - Kamel Qassim Al-Sheakayree, Talib (University of Thi-Qar Journal of Science, 2019)
Gypseous soils are abundant in Iraq, constitute over 33% of total surface area in Iraq. The structures that founded on these soils could face large damages due to dissolving of gypsum when saturated in water.This study investigates the shear strength characteristics of gypseous soil with lime. The soil used was fetched from Al-Dour region (66% gypsum content). This soil was treated with different percentages of Lime (0.5, 1.5, 2.5 and 5%). Test results pointed out that the best treatment percentage to be 1.5.shear strength tests (direct shear tests) conducted in order to study the shear strength characteristics of gypseous soil with Lime and to find the suitable percentage of Lime to improve the shear strength characteristics of gypseous soil against the effect of soaking water, in order to attain a sort of simulation with the field conditions; both the unit weight and the water content of the natural soil are kept equal to the field values. All treated specimens were cured at 370C for 7 days before performing these tests. The results of shear strength tests show that the addition of Lime to the gypseous soil increases their strength to an optimum value and then decreases.